Standard method for evaluating the strength of brazed joints (American Welding Society, 2008)
Abstract: This standard describes the test methods used to obtain brazed strength data of the short-time testing of single-lap joints in shear, butt-tension, stress-rupture, creep-strength, four-point-bending, and ceramic-tensile-button-specimens. Specimen preparation methods, brazing procedures, testing techniques, and methods for data analysis are detailed. Sample forms for recording data are presented. A graphical method of data presentation relates shear stress to overlap distance.